EVALUATION OF THE EFFECTIVENESS OF USING EDUCATIONAL RESOURCES IN EDUCATION WITH THE HELP OF SOCIAL NETWORKS (Web of Technology: Multidimensional Research Journal, 2023)
This article explores the demand for resources for youth by announcing options to the public via social media that can be used to create a range of educational resources for youth through social media.